Pengembangan Sistem E-Commerce Berbasis Opencart untuk Mendukung Pertumbuhan UMKM di Sumatera Barat - Rahmadani Daulay, Fitri; Annas, Firdaus; Fahira Risna, Rahma (Yayasan Lembaga Studi Makwa, 2024)
The development of an OpenCart-based e-commerce system is a strategic step in supporting the growth of micro, small and medium enterprises (MSMEs) in West Sumatra. Business sectors such as the manufacture of sanjai crackers and handicrafts are examples of areas that can utilise this platform to improve competitiveness and expand market reach. Business digitalisation through e-commerce allows businesses to more easily promote their products, reach consumers in various regions, and improve operational efficiency. This research aims to analyse the implementation of OpenCart in improving the accessibility and marketing of MSME products. The research method used is a case study with a qualitative approach and Research and Development (RND). Data collection was conducted through in-depth interviews with MSME owners as well as secondary data analysis from various related reports. This approach allows the research to gain an in-depth understanding of the challenges and opportunities faced by MSME players in adopting digital technology. The results show that the use of OpenCart can significantly increase product visibility, expand market reach, and simplify the transaction process. With this e-commerce system, MSME players can manage their online stores more efficiently, manage product catalogues, and optimise digital marketing strategies. In addition, training in the use of e-commerce platforms has proven to be very important so that MSME players can make optimal use of technology. In conclusion, the development of an OpenCart-based e-commerce system can be an effective solution in supporting the growth of MSMEs in West Sumatra. With proper implementation, this platform can help improve the competitiveness of local products in the digital market, both at the national and international levels. The adoption of digital technology in MSME businesses also has the potential to accelerate digital-based economic transformation and create new opportunities for small businesses to be more competitive in the era of globalisation.